2003
DOI: 10.1071/mr03007
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The reproductive behaviour of four intertidal and two subtidal mussel populations were investigated within two spatial scales at Ninety Mile Beach, northern New Zealand, where large quantities of seed mussels are collected for aquaculture. Reproductive cycles were compared between intertidal and subtidal populations and among intertidal populations along a 90-km coastal area. Histological sections of mussel gonads were used to identify the reproductive state of individual mussels collected monthly between July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In P. viridis, major spawning occurs during June to September with settlement from August to December. Spatial variation in size specific reproductive output could also have important consequences for recruitment as has been described for P. canaliculus and M. californianus (Alfaro et al, 2003;Phillips, 2007). Settlement occurs at low intensities throughout the year and intense settlement occurs during post monsoon (Kuriakose et al, 1984;Hunt and Scheibling, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In P. viridis, major spawning occurs during June to September with settlement from August to December. Spatial variation in size specific reproductive output could also have important consequences for recruitment as has been described for P. canaliculus and M. californianus (Alfaro et al, 2003;Phillips, 2007). Settlement occurs at low intensities throughout the year and intense settlement occurs during post monsoon (Kuriakose et al, 1984;Hunt and Scheibling, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive behavior of the green lipped mussel P. canaliculus has been described by Buchanan (2001) and Alfaro et al (2001Alfaro et al ( , 2003. Settlement and recruitment patterns in Mytilus galloprovincialis and M. canaliculus have been detailed by Peteiro et al (2007) and Phillips (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies carried out by Buchanan and Babcock [8] found that the Greenshell TM Perna canaliculus mussel goes through two settlement phases, as postulated in Bayne's primarysecondary settlement model. In more recent studies, Alfaro and Jeffs [9] observed that P. canaliculus mussel larvae undergo transition from planktonic to sessile life during their primary settlement, then metamorphosing into juveniles. Free-floating macroalgae were thought to be the substrates on which the larval primary settlement occurs, also providing transportation towards rocky shores [10].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies exposed that the spawning of mussels is largely influenced by temperature, salinity, and food availability [20,21]. Moreover, habitat was also found to influence the reproduction of mussels, where subtidal population had consistently higher gonad indices and prolonged reproductive maturity compared to the intertidal population [22].…”
Section: Introductionmentioning
confidence: 99%